In Vivo and in Vitro Toxicity Studies of Aqueous Extract of Mas Cotek (Ficus Deltoidea) - Mohd Saaya, Fazliana (2010)
Ficus deltoidea or its local name “mas cotek” was never been studies before about their safety and toxicity although this herbal has been used for a long time. Lack of reports on the safety and toxicity of this herbal plant will lead to the abuse usage and wrong interpretation on its benefit to human body. Therefore the present study was designed to evaluate the safety and toxicity profile of aqueous extract of F. deltoidea based on hematological, biochemical and target organ toxicity studies by in vivo method and also genotoxicity and cytotoxicity effect by in vitro methodology. In the acute toxicity test, oral administration of 3g/kg of F. deltoidea produced neither mortality nor changes in behavior or any other physiological activities. In subchronic toxicities studies, no changes in organ weight and body weight was observed when the three doses of 100, 300 or 600 mg/kg of aqueous extract of F. deltoidea were administered orally for a period of 90 days. In the blood chemistry analysis, no significant changes occurred, with the exception of a rise in ALT, total protein and urea parameters and decreases in sodium and chloride concentration. Hematological analysis showed no differences in any of the parameters examined. Pathologically, neither gross abnormalities nor histopathological changes were observed. From in vitro cytotoxicity studies results showed that F. deltoidea aqueous extract did not exhibit strong cytotoxicity effect at the dose concentration less than 4000 μg/ml. But with increased concentrations up to 8000 μg/ml, F. deltoidea aqueous extract produced cytotoxicity effect to the liver cell. In genotoxicity studies, at the dose concentration of 4000 μg/ml F. deltoidea aqueous extract has no potential to induce single-strand DNA breaks when assessed using the comet assay. In visual scoring the cell was remained in score 0 to 1 and calculation of tail intensity and tail moment also showed that no DNA damage was occurred. In conclusion, administration of aqueous extract of F. deltoidea was considered safe based on its effect on in vivo and in vitro studies. Meanwhile, further studies on its effect on the fetus in pregnant animals, on the reproductive capacity of animals and on the genetic system are needed to complete the safety profile of this herbal plant.